Time Scales of Fickian Diffusion and the Lifetime of Dynamic Heterogeneity - Das, Rajsekhar; Dasgupta, Chandan; Karmakar, Smarajit (Frontiers in Physics, 2020)
Dynamic heterogeneity, believed to be one of the hallmarks of the dynamics of supercooled liquids, is expected to affect the diffusion of the particles comprising the liquid. We have carried out extensive molecular dynamics simulations of two model glass-forming liquids in three dimensions to study the time scales at which Fick's law of diffusion starts to set in. We have identified two different Fickian times cales: one at which the mean squared displacement begins to show a linear dependence on time, and another one at which the distribution of particle displacements becomes Gaussian. These two times scales are found to be very different from each other and from the α relaxation time in both systems. An interesting connection is found between one of these Fickian time scales and the time scale obtained from the bond-breakage correlation function. We discuss the relation among these different times cales and their connection to dynamic heterogeneity in the system.